Multiple sclerosis progression: time for a new mechanism-driven framework. Issue 1 (January 2023) - Kuhlmann, Tanja; Moccia, Marcello; Coetzee, Timothy; Cohen, Jeffrey A; Correale, Jorge; Graves, Jennifer; Marrie, Ruth Ann; Montalban, Xavier; Yong, V Wee; Thompson, Alan J; Reich, Daniel S; ,; et al.
Summary: Traditionally, multiple sclerosis has been categorised by distinct clinical descriptors—relapsing-remitting, secondary progressive, and primary progressive—for patient care, research, and regulatory approval of medications. Accumulating evidence suggests that the clinical course of multiple sclerosis is better considered as a continuum, with contributions from concurrent pathophysiological processes that vary across individuals and over time. The apparent evolution to a progressive course reflects a partial shift from predominantly localised acute injury to widespread inflammation and neurodegeneration, coupled with failure of compensatory mechanisms, such as neuroplasticity and remyelination. Ageing increases neural susceptibility to injury and decreases resilience. These observations encourage a new consideration of the course of multiple sclerosis as a spectrum defined by the relative contributions of overlapping pathological and reparative or compensatory processes. New understanding of key mechanisms underlying progression and measures to quantify progressive pathology will potentially have important and beneficial implications for clinical care, treatment targets, and regulatory decision-making.